Does Capital Intensity And Profitability Affect Tax Aggressiveness? (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to determine the effect of capital intensity and profitability on tax aggressiveness. The research method used in this research is explanatory. The data analysis method used is panel data regression analysis. Sources of data for this study are data in the form of annual financial statements of mining sector companies listed on the Indonesia Stock Exchange (IDX) in 2017-2019. The population in this study was 141 observations. The sampling technique used in this study was purposive sampling, the total sample is 30. The results show that capital intensity and profitability partially affect tax aggressiveness.